Causes, factors, and complications associated with hospital admissions among patients with Parkinson's disease - Shaibdat, Navena Sharma; Ahmad, Norfazilah; Azmin, Shahrul; Ibrahim, Norlinah Mohamed (Frontiers in Neurology, 2023)
Introduction Patients with Parkinson's disease (PD) are at a higher risk of hospital admissions compared to the general population. We studied the causes and factors associated with admissions among patients with PD over 6 years. Methods We included all PD admissions between 1 January 2016 and 31 December 2021. Other causes of parkinsonism were excluded. Causes of admissions were divided into PD-related (direct or indirect) or non-PD-related. The type of admission was categorized into emergency or elective. Results We identified 605 hospital admissions (259 patients with PD); 345 (57.0%) were PD-related and 260 (43%) were non-PD-related. Emergency PD admissions contributed to 50.4% of all admissions, most commonly from respiratory infection (23%). PD admissions in comparison to non-PD admissions were associated with worse disease severity (HY ≥ 3; p < 0.001), longer disease duration [8.71 (SD 6.23) vs. 6.60 (SD 5.39) years; p < 0.001], and longer hospital stay [7.70 (SD 5.89) vs. 6.42 (SD 7.63) days; p = 0.020]. Non-PD admissions were associated with more comorbidities (97.3%; p = 0.013). There were 124 (20.5%) complications and 31 deaths (5.1%). A total of 29 deaths were due to respiratory infection and 3 deaths were due to COVID-19 pneumonia. Emergency admission (PD- and non-PD-related; p = 0.001) and respiratory-related causes (p < 0.001) were predictors of unfavorable hospital admission outcomes (death and complications). Conclusion Respiratory infection was the leading cause of hospital admission and a significant independent predictor of unfavorable hospital admission outcomes (death and complications). PD-related admissions were associated with disease severity and led to more complications and longer hospital stays. Non-PD-related admissions were associated with comorbidities.